The Mediating Effect of Leader Accountability on the Relationship between Transcendental Leadership of School Heads and Teacher Self-Efficacy - Cindy Gonzalez; Ester Jean U. Pelayo (Har Press Indonesia, 2022)
This study investigated the mediating influence of leader accountability on the relationship between transcendental leadership of school heads and teacher self-efficacy in public secondary schools in two municipalities of Davao Oriental. (Failure of teachers to maintain and improve their own performance in the classroom can have a significant impact on the students' learning. The ineffectiveness of teachers has an influence on the entire educational system. Teachers that are inept will have a detrimental influence on student learning results. Self-efficacy relates to one's belief in one's own skills and inefficiencies, which may lead to a number of psychological issues such as low confidence and low self-esteem). A stratified random sample approach was adopted, with 300 teachers serving as respondents. The findings of a non-experimental quantitative mediation study using medgraph, a validated questionnaire, mean, regression procedures, and Pearson r revealed substantial correlations between school leaders' transcendental leadership, teacher self-efficacy, and leader accountability. The mediating influence of leader accountability on the relationship between school leaders' transcendental leadership and teacher self-efficacy was partial. As a result, one of the ways that transcendental leadership of school heads may influence teacher self-efficacy is through leader accountability. However, this does not fully explain the relationship between the two variables.